Differentiated Instruction in German Classes (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the problems of the methodology of a differentiated approach to students in teaching the German language. It also deals with the main objectives of the differential approach in teaching a foreign language, the cognitive needs of students, individual preparedness, individual qualities of each student.